Pilot study of propranolol premedication to reduce FDG uptake in brown adipose tissue on PET scans of adolescent and young adult oncology patients. (3rd April 2017) - George, Anil; Sinha, Partha; Conrad, Gary; Memon, Aum A.; Dressler, Emily V.; Wagner, Lars M.
ABSTRACT: Objective: Physiologic uptake of 18 F-fluorodeoxyglucose (FDG) in brown adipose tissue (adipose tissue) of cancer patients may confound interpretation of positron emission tomography (PET) scans. Uptake in adipose tissue occurs in up to half of pediatric oncology patients undergoing PET scans, and is especially common in adolescents. adipose tissue is innervated by the sympathetic nervous system, and beta blockers such as propranolol have shown efficacy in reducing adipose tissue uptake on PET scans done in older adult oncology patients.Participants: Because propranolol may cause hypoglycemia or other side effects in fasting patients, we prospectively assessed the safety of a single dose of 20 mg propranolol in adolescent and young adult oncology patients undergoing FDG-PET imaging.Methods: Ten patients (median age 18 years, range 14–24) received propranolol premedication prior to FDG-PET.Results: No adverse effects or clinically significant changes in serum glucose, heart rate, or blood pressure were observed. Five of the 10 patients had adipose tissue identified on previous PET scans. However, following propranolol administration only, one patient had persistent uptake in adipose tissue.Conclusions: Propranolol was convenient and safe in fasting adolescent and young adult oncology patients undergoing PET scans. Larger studies are warranted to better define the effectiveness of this approach.